2020
DOI: 10.1155/2020/5246504
|View full text |Cite
|
Sign up to set email alerts
|

Primary Angioplasty in a Catastrophic Presentation: Acute Left Main Coronary Total Occlusion—The ATOLMA Registry

Abstract: Objectives. To determine the outcome predictors of in-hospital mortality in acute total occlusion of the left main coronary artery (ATOLMA) patients referred to emergent angioplasty and to describe the clinical presentation and the long-term outcome of these patients. Background. ATOLMA is an uncommon angiographic finding that usually leads to a catastrophic presentation. Limited and inconsistent data have been previously reported regarding true ATOLMA, yet comprehensive knowledge remains scarce. Methods. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…In the abovementioned studies and the present study, the only common predictor significantly associated with reduced 30-day survival was successful reperfusion (final TIMI flow 3). Although in the present study, the use of mechanical support was found to be associated with 30-day mortality, in the studies by Galván-Román et al [ 40 ] and Gutiérrez-Barrios et al [ 20 ], this was not observed. In the study by Galván-Román et al [ 40 ] and the present study, mechanical support was inserted before PCI in the majority of cases.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…In the abovementioned studies and the present study, the only common predictor significantly associated with reduced 30-day survival was successful reperfusion (final TIMI flow 3). Although in the present study, the use of mechanical support was found to be associated with 30-day mortality, in the studies by Galván-Román et al [ 40 ] and Gutiérrez-Barrios et al [ 20 ], this was not observed. In the study by Galván-Román et al [ 40 ] and the present study, mechanical support was inserted before PCI in the majority of cases.…”
Section: Discussioncontrasting
confidence: 76%
“…In the present study, the incidence was 0.50%, a discrepancy related to the fact that previous studies also included subtotal occlusion or critical stenosis of the LMCA. The present study exclusively included patients with total occlusive ULMCA AMI referred for primary angioplasty and is in line with the findings of the Acute Left Main Coronary Total Occlusion (ATOLMA) Registry, as they reported an incidence of 0.58% [ 20 ]. Presumably, the true incidence of ULMCA lesion-related AMI may be underestimated as patients in this clinical setting may die before they reach hospital.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The retrograde approach was attempted if the anterograde approach failed for more than 1 hour and if the approach through the collaterals was feasible. The outcome of PCI was defined as a success if the successful opening of total occlusion and restoring flow was achieved (<30% residual stenosis and TIMI ≥2 flow) (1,23). If the guidewire was consistently unable to pass through the occluded segment, or if severe dissection, perforation, and other complications of coronary artery occurred, the operation was terminated and defined as PCI failure (24).…”
Section: The Ica and Pci Proceduresmentioning
confidence: 99%